Criminal Responsibility of Artificial Intelligence Committing Deepfake Crimes in Indonesia - Asri Gresmelian Eurike Hailtik; Wiwik Afifah (Pelopor Publikasi Akademika, 2023)
The development of technology that continues to evolve has given birth to an innovation called artificial intelligence or artificial intelligence which is usually called